2016
DOI: 10.1016/j.oraloncology.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarettes induce DNA strand breaks and cell death independently of nicotine in cell lines

Abstract: Objectives Evaluate the cytotoxicity and genotoxicity of short- and long-term e-cigarette vapor exposure on a panel of normal epithelial and head and neck squamous cell carcinoma (HNSCC) cell lines. Materials and Methods HaCaT, UMSCC10B, and HN30 were treated with nicotine-containing and nicotine-free vapor extract from two popular e-cigarette brands for periods ranging from 48 hours to 8 weeks. Cytotoxicity was assessed using Annexin V flow cytometric analysis, trypan blue exclusion, and clonogenic assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
213
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(224 citation statements)
references
References 30 publications
7
213
0
4
Order By: Relevance
“…Most of studies addressed the effect of e-cigarette in heart rate, blood pressure or heart beat instead of palpitations. Increased heart rate is a common finding 7,16 . Following short time e-cigarette use, a statistically significant decrease in oxygen saturation (SpO2) was noted in COPD patients who had already a lower baseline level compared with the other smoker groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of studies addressed the effect of e-cigarette in heart rate, blood pressure or heart beat instead of palpitations. Increased heart rate is a common finding 7,16 . Following short time e-cigarette use, a statistically significant decrease in oxygen saturation (SpO2) was noted in COPD patients who had already a lower baseline level compared with the other smoker groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cell lines, e-cigarette vapour increases oxidative stress, inflammation 4,5 , may influence susceptibility to virus infection 6 and induces DNA strand breaks and cell death 7 on airway epithelial cells. It is also cytotoxic, induces apoptosis in fibroblats 8 , initiate inflammation at Kupffer 9 and enthothelial 10 cells, and alters vascular smooth muscle cells 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Los datos recientes sobre la prevalencia de los cigarrillos electrónicos en muestras europeas y americanas indican que, hasta la fecha, casi el 6,8% de adultos usa los cigarrillos electrónicos (McMillen, Gottlieb, Shaefer, Winickoff, y Klein, 2015). No obstante, esta popularidad creciente ha generado un debate en la salud pública respecto de su seguridad y efectividad como alternativa de cesación tabáquica (Yu et al, 2016). Estudios sobre los cigarrillos electrónicos y la cesación tabáquica han ofrecido resultados mixtos.…”
unclassified
“…What is more, Farsalinos et al 17 showed that cinnamon-flavored liquids have a cytotoxic influence on myoblasts isolated from rats' hearts. Furthermore, Yu et al 18 presented findings of changes in the DNA which resulted from e-cigarette aerosol, which were similar to those caused by tobacco smoke.…”
Section: Discussionmentioning
confidence: 83%